Use of the International Classification of Functioning Disability and Health (ICF) as a theoretical framework to inform interprofessional assessment and management by health care professionals in Rwanda.: a cluster randomised control trial - Sagahutu; Jean Baptiste (Department of Health and Rehabilitation Sciences, 2018)
Background: Effective collaboration between health professionals can reduce medical errors and assist in interpretation of health information resulting in improved patient care. The International Classification of Functioning, Disability and Health (ICF) has been suggested as a potential framework to help health professionals develop a common language for better collaboration and to provide more holistic care. In the main, Rwandan district hospitals still utilise the hierarchical medical model of health. Aim: The aim of the study was to determine whether training on interprofessional practice, using the ICF framework, resulted in improved knowledge, attitudes and behaviour(as determined by improved recording of interprofessional assessment and management in patient records) in randomly selected Rwandan District Hospitals. Methodology: This study was composed of two phases. Phase I: Preparation. The intervention programme was developed based on a literature review and input from an international panel of experts. A feasibility study in which self-designed instruments and the training programme were tested was undertaken in one district hospital. Phase II: A Cluster Randomised Control Trial. Four district hospitals were randomly allocated to receive a day’s training in interprofessional practice using the ICF (experimental hospitals) or a short talk on the topic (control hospital). Participants included medical doctors, nurses, physiotherapists, social workers, nutritionists, and mental health nurses/clinical psychologists. Using self-designed and validated measures, pre- and postmeasurements of knowledge and attitudes towards Interprofessional Practice (IPP) were performed at baseline and after training and audit of patients’ records after discharge was performed at baseline and at two, four and six months. The independent t-test and Mann-Whitney U test were used to establish if the two sets of groups were equivalent before and after training at baseline and at two, four and six months. Repeated measures ANOVA and the post-hoc Tukey test were used to compare the audit scores at each time point. The Kruskal Wallis test was used to compare rankings of the scores of attitudes of different professions before and after the intervention. Ethical approval was obtained from the Human Research Ethics Committee of the University of Cape Town and the Rwandan National Ethics Committee.